Total amount of money Minah and Rohana had = $338
Let us assume the amount of money Minah have initially = x dollars
Let us also assume the amount of money Rohana had initially = y
Then
x + y = 338
y = 338 - x
And
x + 49 = y/2
2x + 98 = y
2x - y = - 98
Now let us put the value of y found from the first equation in the second equation.
2x - y = - 98
2x - (338 - x) = - 98
2x + x - 338 = - 98
3x = 338 - 98
3x = 240
x = 240/3
= 80 dollars
So the amount of money that Minah had at first is $80. I hope the procedure is clear enough for you to understand.